Assessment of the marketing activities of private healthcare providers aming female decision makers - Katona, Norbert; Rita, Szabó; Szeberényi, András (Studia Mundi – Economica, 2023)
The field of healthcare marketing is currently at the centre of lively scientific and practical interest, which appreciates the importance of knowing and influencing consumer decisions. Healthcare marketing was strongly affected by the COVID situation, the emergence of social media platforms, and the advancement of influencer marketing, while literature indicate that women have a prominent role in making consumer decisions. The objective of our large-scale (n=1836) online survey was to quantitatively examine the online marketing communication and social media activities of private healthcare providers in Hungary. We focused on whether the marketing activities of private healthcare services, their activity on social media platforms meet the expectations of the Budapest and Pest County women, and whether the opinions of well-known/famous people have a positive influence on their consumer decisions. According to our findings, social media platforms are of particular importance, but they believe that advertisements about health services appearing in the digital space are less trusted, especially regarding older respondents. When choosing a service provider, the expressions of acquaintances in their circle of acquaintances who have already gained experience with the given practice proved to be the most important, which point in the direction of building ambassador systems made up of loyal patients.